Design of right angle slot antenna for dual band and dual polarized with wireless network - Pomsathit, A.; Benjangkaprasert, C.; Anantrasirichai, N.; Rakluea, Paitoon; Wakabayashi, T. (My University, 2010)
A novel compact and light weight antenna for dual band and dual polarized right angle slot antenna fed by micorstrip line use in wireless network technology is designed. The antenna composed of three right angle slot radiators on a same ground plane. Two right angle slots in the same size are arranged for circularly polarized at frequency 4.95 GHz and the other one is designed for linearly polarized at frequency 2.45 GHz. Therefore, in order to achieve dual band and dual polarized with good matching, the technique of arrangement is recommended. The simulation results of return loss, VSWR, gain, axial ratio, and radiation patterns are shown at resonant frequency 2.45 GHz and 4.95 GHz. ©ICROS.
Keywords: Dual band; Dual polarized; Right angle slot antenna